Esprue Celíaco: A Propósito de un Caso en el Hospital Nacional Daniel A. Carrión - Trigoso Ruiz, Víctor (1998)
We report a case of celiac sprue in an adult patient , male , with antecedent chronic diarrhea of 30 years of evolution in several previous hospitalizations and opportunities being discharged without a definite etiology. The diagnosis was made based on the following criteria : Existence of impaired absorption of one or more nutrients at the level of the mucosa of the small intestine , demonstrating the histopathological changes at that level features and forwarding them after a suitable period of specific treatment with gluten free diet. The gliadin antibody serology positive IgA + IgG was found. Clinical recovery was satisfactory. As a contribution to the casuistry of this rare disease presenting this case is the first in both the Medical Service Men and the HNDAC . A review of the most important features that accompany this disease becomes .